Selective Norm Internalization: Reframing the Global–Local Tension in LGBT Debates in Indonesia - Rachmayani; Netik Indarwati; Muhammad Hardiansyah (Indonesian Journal Publisher, 2026)
The diffusion of global norms has increasingly shaped debates on social values, identities, and human rights across different societies, including Indonesia. Among these debates, LGBT issues have emerged as a particularly contested arena where internationally promoted norms intersect with locally embedded cultural, religious, and ideological traditions. This study examines how the legitimacy of globally promoted LGBT-related norms is negotiated within Indonesia's existing normative order, with particular attention to the role of Pancasila as the country's foundational normative framework. Using a qualitative case study approach, the research draws upon interviews, questionnaire responses, and document analysis involving LGBT communities, human rights advocates, religious leaders, and state-related institutions. The findings reveal that globalization has expanded the visibility of LGBT discourse through digital media, transnational advocacy networks, multinational corporations, and global cultural flows. However, societal responses extend beyond a simple binary of acceptance and rejection. Instead, state institutions, religious organizations, civil society actors, and members of the LGBT community actively evaluate the legitimacy of externally promoted norms according to Indonesia's constitutional, moral, and cultural foundations. Building on these findings, this article proposes the concept of Selective Norm Internalization to explain how external normative claims acquire, negotiate, or fail to acquire legitimacy within a normative architecture grounded in Pancasila. The study contributes to International Relations scholarship by shifting analytical attention from the diffusion of global norms toward the question of normative legitimacy, demonstrating that the authority to determine the acceptability of external norms remains embedded within locally constituted normative frameworks.